The Nature of Technology Implications for Learning and Teaching - Clough, Michael P.; Olson, Joanne K.; Niederhauser, Dale S.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
How does technology alter thinking and action without our awareness? How can instantaneous information access impede understanding and wisdom? How does technology alter conceptions of education, schooling, teaching and what learning entails? What are the implications of these and other technology issues for society? Meaningful technology education is far more than learning how to use technology. It entails an understanding of the nature of technology $1 (Bwhat technology is, how and why technology is developed, how individuals and society direct, react to, and are sometimes unwittingly changed by technology. This book places these and other issues regarding the nature of technology in the context of learning, teaching and schooling. The nature of technology and its impact on education must become a significant object of inquiry among educators. Students must come to understand the nature of technology so that they can make informed decisions regarding how technology may influence thinking, values and action, and when and how technology should be used in their personal lives and in society. Prudent choices regarding technology cannot be made without understanding the issues that this book raises. This book is intended to raise such issues and stimulate thinking and action among teachers, teacher educators, and education researchers. The contributions to this book raise historical and philosophical issues regarding the nature of technology and their implications for education; challenge teacher educators and teachers to promote understanding of the nature of technology; and provide practical considerations for teaching the nature of technology.s
Keywords: Education; Education; Education (general).